ASSESSMENT OF NATURAL RESOURCES FOR MARINE TOURISM OF SMALL ISLANDS IN THE ARU ISLANDS, MALUKU - Dyah Widiyastuti (Centre For Tourism Planning and Development, 2018)
Abstract. Marine tourism is an important attraction of natural tourism Indonesia today. Consisting of small islands and considered as outer region, Aru Islands, as one of the districts in the Maluku province has potential for marine tourism-based coastal and small islands supported cultural potential, so it is suitable to be developed as a maritime destination. Marine tourism should be managed with conservation and ecological approach to community-based, it is in accordance with the conditions in which the tourist sites in the coastal area adjacent to the local community. The aims of this study were to identify potential marine tourism Aru Islands; to identify issues, challenges and formulate strategies and recommendations for marine tourism development that capable of accommodating the interests of society also the conservation of coastal and small islands. Resources for development of nature-based marine tourism were identified and assessed in the Aru Islands. The study results showed that as an archipelago, the Aru Islands have some 42 potential and attractiveness of a total of 88 marine tourism potential and attractions. Aru Islands also has unique and distinctive cultural and culinary for supporting the development of marine tourism. As a new destination, Aru Islands need a comprehensive and holistic development strategy. The approach includes physical and infrastructure improvement, management and institutions, marketable tourism products, and the development of a host community. These approaches to ensure tourism development in Aru Islands grow sustainably.